Efficient On-Line Traffic Policing in Software Defined Network - Qian, Lie (Discoveries in Agriculture and Food Sciences, 2018)
On-line traffic such as conversational call and live video on the Internet are not pre-recorded and has no exact information about each session before the traffic happens. S-BIND (Confidence-level-based Statistical Bounding Interval-length Dependent) traffic model characterizes such traffic for QoS admission (GammaH-BIND) and policing purpose. A state-dependent token bucket based statistical regulator was proposed to police the traffic using S-BIND parameters. Recently, Software Defined Network (SDN) is proposed to decouple the control plane from the data plane, which enables low cost commodity design in switches and flexible network feature deployments through software implementation in centralized controllers. To deploy the state-dependent token bucket statistical regulator in SDN, extensions to the current SDN are needed. In this paper, design options for S-BIND traffic regulator in SDN switches are presented and analyzed. Among these options, a single meter design is chosen based on the cost and efficiency comparison between them. The needed switch implementation and OpenFlow protocol’s extensions to realize the regulator in SDN is given at the end of the paper.